Model Berdayakan Muallaf Lazismu di Daerah 3T, Suku Abun di Kabupaten Sorong - Santoso, Budi Santoso; Jaharudin, Jaharudin; Mulloh, Farcham; Suprapto, Rohmat (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2021)
Zakat Institution Infaq and Shadaqah Muhammadiyah Sorong regency is a zakat institution or zakat collecting institution that serves in community empowerment activities through productive utilization of zakat funds, infaq, wakaf and other generosity. One of its flagship programs is the construction of the Abun Tribe of Sorong Regency. The construction of the Abun tribe continues as a form of Lazismu's concern for vulnerable groups (muallaf). The purpose of this research is to describe the contribution that lazismu has made in the development of muallaf Abun tribe of Sorong district. This research includes descriptive-qualitative research data excavated using observation techniques, interviews and documentation. After the data collected, qualitative data analysis is carried out using Miles and Huberman analysis. The results showed that: Muhammadiyah da'i program, social service activities: Eid al-Qurban activities, spraying disinfectant during the Covid-19 pandemic.